Does The Market React To The Implementation Announcements Of The Malaysian Capital Market Masterplan Initiatives? - Tium, Jimmy Beng Teck (2006)
This dissertation investigates the market reactions to announcements of the implementation of the Malaysian Capital Market Masterplan (CMP) initiatives related to equity market in the local exchange. An event study methodology was employed in this study. While Kuala Lumpur Composite Index, EMAS Index and Second Board Index were used as proxies for the market returns, the Morgan Stanley Capital International’s Emerging Markets Index was used as proxy for the broader global market returns. In order to test for the vigorousness of the findings, the study adopted two empirical models used by Riley and Luksetich (1980) and Kritzman (1994). In addition to the parametric tstatistic test, the non-parametric Corrado rank test was also used to increase the statistical power of the study and to ascertain the robustness of the results. An exploratory mini survey was also carried out on the corporate finance practitioners to identify the possible justifications of the findings.The findings based on Riley Model showed that the market, regardless whether it represented active, large or small capitalisation companies, did not react significantly to the announcements of the implementation of CMP initiatives at 0.05 level. Similar findings were obtained in the Kritzman Model. The results were robust as evident in the Corrado rank test at the same 0.05 level of significance. The corporate finance practitioners who participated in the mini survey had overwhelmingly concurred that the market could not comprehend the benefits to be derived from the CMP initiatives. While that might explain the non-reaction of retail investors, the non-reaction of institutional investors might be due to the perceived unsatisfactory level of corporate governance. The lack of understanding and the eroded investor confidence could have overshadowed the expected benefits of the CMP initiatives. While the roles of market intermediaries and print media in educating the investors are essential to improve market efficiency, the restoration of investor confidence through higher standard of corporate governance is also fundamentally important to encourage investors’ participation in the market. It is only with improved efficiency and investor confidence that the market will act more rationally, and any measures to shape the local capital market can then be implemented more effectively.